Regulatory Arrangements and Utilization of Artificial Intelligence (AI) in Realizing Personal Data Protection in Indonesia - Putri Adytia, Nur Amalina; Arief, Sofyan; Astesa, Duflitama (KnE Social Sciences, 2024)
Indonesia has several legal instruments for personal data protection that are scattered and only adapt to the main contents of each law, so the legal protection provided is still not optimal. This study aims to examine the use of Artificial Intelligence (AI) as a tool to protect personal data and to examine the urgency of a special regulation in Indonesia to protect personal data. This research method employs both a statutory and a comparative legal approach. The research indicates that it is imperative for the Indonesian government to establish and ratify a dedicated legal framework for safeguarding personal data without delay. Furthermore, leveraging the potential of AI presents a promising opportunity to maximize the protection of personal data.. The use of AI in personal data protection will minimize the occurrence of human errors so that personal data protection can be more secure. Keywords: personal data, artificial intelligence, protection, urgency